Empirical Power and Scaling laws of Quito, Guayaquil and other cities in Ecuador - Felipe Vaca Ramírez; Bolívar Morales Oñate; Carlos Jiménez Mosquera (ACI Avances en Ciencias e Ingenierías, 2015)
Several papers have shown that distributions characterized by mean and variance are inappropriate for accounting spatial or geographic patterns. The reason is data is not accumulated around a central value; rather, tails become heavy and extreme events result less unlikely than under other distributions. In this sense, this work aims to find empirical laws on some relevant variables of cities in Ecuador, For this purpose, we start from two hypothesis: 1) some socioeconomic variables scales from a size variable, and 2) such variables follow a power law distribution; then estimate needed parameters, and carry out contrasts with adequate heavy tail distributions.